An empirical study of servant leadership on the performance of small and medium-sized enterprises in Malaysia / Raja Rizal Iskandar Raja Hisham ... [et al.] - Raja Hisham, Raja Rizal Iskandar; Ismai, Saiful Azizi; Abd Manan, Elina; Ramli, Muhamad Rahimi (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
Although previous studies have addressed the effect of leadership and performance of Small and Medium-sized Enterprises (SMEs), however, little attention has been given by researchers to observe the effect of servant leadership in enhancing SME performance. Thus, the purpose of this study was to examine the theoretical model of servant leadership on the performance of SMEs. The model was grounded in the Revised Servant Leadership Theory and Path-goal Theory. A quantitative approach-based survey was carried out to obtain data from SME employees. A total of 200 companies were surveyed via the convenience sampling technique and only 104 usable data were used in the analysis. The Partial Least Squares Structural Equation Modelling (PLS-SEM) approach was utilized to assess the hypotheses. The results of the study indicate that servant leadership is an important predictor to enhance SME performance. Path analysis confirms that emotional healing, wisdom, and organizational stewardship were significantly related to SME performance. On the contrary, altruistic calling and persuasive mapping were found not to influence SME performance. This study provides a basis for further improvements in the application of the model while companies may focus on the stewardship aspect to ensure that employees are not left behind in achieving success. The theoretical and practical contributions of the study are also discussed, and suggestions are given for future research.